PENGARUH VARIASI MASSA ZEOLIT PADA PENGOLAHAN AIR LIMBAH PABRIK PAKAN TERNAK MELALUI MEDIA FILTRASI - Sumarli Sumarli; Ian Yulianti; Masturi Masturi; Rosyidatul Munawaroh (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
The processing of the feed mill wastewater has been done through the filtration media by varying the zeolite mass to know the influnce of zeolite mass variation on several parameters, namely of clarity, the value of TDS and pH of the wastewater feed mill filtrate. The filtration process was done by using a variation of the zeolite mass of 200g, 300g, 400g, 500g and 600g. Other materials were used as a filtration media was the active carbon, silica sand, and gravel with a mass of 200g has been controlled. The results showed that the processing of the feed mill wastewater by varying the mass of zeolite through filtration media could improved water quality of processing results. In this study the sample was using a zeolite mass of 600g has the highest level of clarity, with a value of TDS 844ppm and pH 7.8. Keywords: zeolite, filtration, wastewater, animal feed.